How Rebate Bans, Discriminatory MLS Listing Policies, and Minimum Service Requirements Can Reduce Price Competition for Real Estate Brokerage Services and Why It Matters - Matthew Magura (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
Institutional characteristics of a typical residential real estate transaction may create a causal link between commission rate reductions and service degradation. Such a link mitigates agents' incentive to compete on commission rates. Rebate bans, discriminatory MLS listing policies, and minimum service requirements strengthen the link thereby frustrating greater commission rate competition. Eliminating rebate bans, discriminatory MLS listing policies and minimum service requirements will increase commission rate competition and reduce wasteful rent seeking by agents.
Keywords: 330